2020
DOI: 10.5267/j.msl.2020.4.003
|View full text |Cite
|
Sign up to set email alerts
|

Elements influence international tourists’ satisfaction

Abstract: This study attempted to identify decisive factors having important impacts on international tourists' satisfaction in Ho Chi Minh City (HCMC). By conducting a survey of 2,073 foreign visitors in HCMC, this paper explored nine determinants and their effect levels on international tourists' destination satisfaction. Quantitative approach was mainly applied with statistical techniques used as exploratory factor, reliability, and multiple regressions analyses. The result indicated that eight out of nine factors si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Similarly, the authors of [24], when investigating the factors that impact the satisfaction of tourists in a city in Vietnam, found empirical evidence that, among other factors such as historical and cultural attractions, infrastructure services have a significant impact on the satisfaction of tourists. In the same sense, the authors of [25] identified, through an exploratory investigation using a sample of 155 tourists in Vietnam, that infrastructure services, together with the safety of tourists, are a factor of significant influence for the profitability of tourism companies.…”
Section: Transport and Regional Developmentmentioning
confidence: 96%
“…Similarly, the authors of [24], when investigating the factors that impact the satisfaction of tourists in a city in Vietnam, found empirical evidence that, among other factors such as historical and cultural attractions, infrastructure services have a significant impact on the satisfaction of tourists. In the same sense, the authors of [25] identified, through an exploratory investigation using a sample of 155 tourists in Vietnam, that infrastructure services, together with the safety of tourists, are a factor of significant influence for the profitability of tourism companies.…”
Section: Transport and Regional Developmentmentioning
confidence: 96%
“…Therefore, the research of Chi & Qu (2008) and Isa et al (2018) revealed that the components of infrastructure on tourist destination, positively correlates with a good destination and contributes to tourist satisfaction. Thus, tourism infrastructure contributes to tourist satisfaction in the tourist destination (Khuong et al, 2020).…”
Section: Infrastructure On Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…"Tourism infrastructure refers to both the physical and technological facilities created by governments and tourism organizations to capitalize on the potential of tourism, such as hotels and residential complexes, products and services, amusement parks, transportation equipment, and infrastructure works. Infrastructure is a transport network, including road, rail, sea, and air" (Khuong et al, 2020). Furthermore, "tourist pleasure is influenced by location accessibility, including infrastructure, operational variables, government legislation, and equipment" (Virkar and Mallya, 2018).…”
Section: Infrastructure and Tourist Destination Satisfactionmentioning
confidence: 99%